A NOVEL COAXIAL FED PATCH ANTENNAS AT TVWS BAND CHANNELS 24 AND 28 FOR RURAL WIRELESS COMMUNICATION - Yi Lung, Then; Yi Yu, Yap; Chamath Kanalaka, Vithanawasam (The Journal of The Institution of Engineers, 2020)
Microstrip patch antennas are useful for wireless communication as the technology is continuously evolving. Contacting types of microstrip patch antennas, coaxial-probe feeding, will be discussed and designed for the applications of television white space (TVWS). As the digital switchover in many countries is completed or nearly completed, TVWS is desired to be utilized for good purposes. One of them is to provide Internet access. Coaxial-probe fed single-layer single-patch microstrip patch antennas which are directional antennas, are proposed to provide wireless communication in rural areas by broadcasting hotspots. CST Microwave Studio is used to design and simulate the proposed antennas. To widen the bandwidth of the first proposed antenna, improvements are made and can be observed in the rectangular patch antenna with modified U-slots and E-shaped rectangular patch antenna. Both coaxial fed microstrip patch antennas are in good measurements and feasible to cater to the applications of TVWS at the respective channels which are Channel 24 and Channel 28.